2013
DOI: 10.1002/we.1615
|View full text |Cite
|
Sign up to set email alerts
|

Shake table testing and numerical simulation of a utility‐scale wind turbine including operational effects

Abstract: Shake table tests were undertaken on an actual wind turbine (65 kW rated power, 22.6 m hub height and a 16 m rotor diameter) using the Network for Earthquake Engineering Simulation Large High Performance Outdoor Shake Table at the University of California, San Diego. Each base shaking event was imparted in two states, whereas the turbine rotor was still (parked), and while it was spinning (operational). Each state was tested in two orientations of shaking direction, one parallel (fore-aft) and another perpendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…The same observation can be made based on the acceleration profile in the y-direction. The activation of the second FA and SS support structure modes is confirmed by the fact that the acceleration profiles exhibit significant values at approximately 2/3 of the support structure height, and this result is consistent with analogous results for land-based HAWTs under earthquake loading [11].…”
Section: Response To a Single Earthquake Recordsupporting
confidence: 88%
“…The same observation can be made based on the acceleration profile in the y-direction. The activation of the second FA and SS support structure modes is confirmed by the fact that the acceleration profiles exhibit significant values at approximately 2/3 of the support structure height, and this result is consistent with analogous results for land-based HAWTs under earthquake loading [11].…”
Section: Response To a Single Earthquake Recordsupporting
confidence: 88%
“…In particular, comparative analyses in the time domain between the results obtained by fully-coupled simulation performed in GH BLADED [27] and those obtained by linear combination of separate wind and earthquake responses, the latter computed by adding different levels of aerodynamic damping, are carried out. The results show that errors in bending moment and shear forces are within engineering margins, which is encouraging for the use of the uncoupling approach, and confirm that a value of 4% for the aerodynamic damping, recommended by ASCE-AWEA RP2011 [17] and in previous studies [6][7][8][9][10][11][12][13][14][15][16][17][18], can reasonably also be used in time-domain uncoupled analyses.…”
Section: Aeroelastic Model and Decoupled Approachsupporting
confidence: 74%
“…Then, Prowell et al [8] conducted experimental work on a 65 kW Nordtank wind turbine, applying earthquake motions in two horizontal directions, and concluding that the importance of considering seismic demand increases as the turbine grows in capacity. Again, Prowell et al [9,10] showed that earthquakes can produce, in the NREL 5 MW HAWT, a bending-moment demand at the tower base well above the one from extreme wind events in operational, emergency shutdown and parked simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts to study the seismic dynamic responses [6][7][8][9], structural safety [4,5,[10][11][12] and analytical methods [4,13] of wind turbines have been conducted. Most studies focused on onshore wind turbines, which are shorter in the cantilever length than their offshore counterparts.…”
Section: Introductionmentioning
confidence: 99%